As performances do carimbó “pau e corda”: entre batuques e partilha de saberes - Costa, Elyane Lobão da (2022)
The present thesis has as its object the carimbó, as a Cultural Performance. This is a field research, which understands the importance of Collective Memory for the transmission of knowledge. Around this Ancestral Manifestation, there is an exchange of knowledge that is shared between mestres and carimbozeiros, and between mestres and sympathizers, thus marking the cultural identity of these subjects. This cultural manifestation is expressed as music, dance, leisure, religiosity and work, and must be analyzed from different perspectives, thus realizing its symbolic character. From the analysis of the memories of the carimbozeiros masters, it was noticed that the carimbó remains alive through resistance, through the transmission of knowledge through generations and through Non-Formal education, thus being a field of social, political, historical and cultural disputes, thus demarcating the identity of the subjects individually and collectively. The barracões are collective and privileged spaces in which this process of knowledge sharing takes place, thus contributing to a broad training of subjects, focused on citizenship, and the training process plays a fundamental role in safeguarding this cultural asset of an immaterial nature.